The Role of Moderate and Virulent Endogenous Bacteriophages in the Treatment of Pyoinflammatory Infections in Intensive Care Unit Patients - E. B. Lazareva; T. V. Chernenkaya; A. K. Shabanov; N. V. Yevdokimova; E. L. Zhilenkov; M. A. Godkov; S. S. Petrikov (Неотложная медицинская помощь, 2020)
Abstract. In connection with the growth of resistance of pathogens of pyoinflammatory infections (PII) to antibiotics, physicians began to use bacteriophages, which are widespread where there are homologous bacteria. They are also found in the human body, possibly protecting against PII. It was found that mortality in patients with bacteriophages was lower than in patients without homologous endogenous bacteriophages. The most common were mild bacteriophages, which “protected” patients from infection, although it is believed that only virulent bacteriophages may do this.Aim of study. To study the effect of virulent and moderate endogenous bacteriophages on the course of pyoinflammatory infections in intensive care units (ICU) patients.Material and methods. The study included 33 patients with positive blood culture who were treated in the ICU. Of these, 12 (36.4%) had endogenous bacteriophages (10 men, 2 women).We isolated 16 strains of various bacteria. Bacteriological blood tests were performed using an automatic blood culture analyzer Bactec-9050. Identification of isolated microorganisms was carried out using an automatic microbiological analyzer WalkAway 40. Traditional virological methods on the basis of LLC SPC MicroMir were used for work with bacteriophages.Results and discussion. From 16 positive blood cultures, the following were isolated: Klebsiella pneumoniaе — in 7 samples, Acinetobacter spр. — in 4 samples, Staphylococcus spp. — in 2 samples, and one strain in each sample: Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus faecalis. Endogenous phages were isolated in 36.4% of patients, which were detected in all blood cultures. The exception was K. pneumoniae strains, for which in 42.9% of cases (3 cases out of 7) bacteriophages were absent.Out of 12 patients with isolated bacteriophages, 6 had positive treatment outcomes.Of 14 blood samples, 11 moderate bacteriophages were isolated, which amounted to 78.6%, virulent — 21.4%. Despite this, the protective effect of bacteriophages was noted.Conclusion. 1. All blood cultures contained homologous bacteriophages, except K. pneumoniaе strains, which had no endogenous bacteriophages in 42.9% of cases. 2. Most of the isolated endogenous bacteriophages (78.6%) were moderate. 3. In the absence of homologous bacteriophages in the blood of ICU patients, the likelihood of death increases (66.7%) compared to patients with bacteriophages (33.3%).